Expenditure inequality and polarization in Indonesia, 2002-2012. Issue 10 (8th October 2018) - Indra, Indra; Nazara, Suahasil; Hartono, Djoni; Sumarto, Sudarno
Abstract : Purpose: The purpose of this paper is to investigate the relationships between expenditure inequality and expenditure polarization in Indonesia during the post-reformation era in 2002–2012. It also explores the various dimensions of regional groups; and finds out in which dimension did the expenditure inequality and polarization occur in Indonesia during the period. Design/methodology/approach: Gini index was employed to measure expenditure inequality and a number of developed polarization measurement was applied to investigate the linkage between inequality and polarization at national levels. It also applied a polarization index based on inequality decomposition to investigate how the polarization occurs in the regional dimension. It covered several groups of regional dimensions; those are rural and urban areas; eastern and western regions, as well as natural resource-rich provinces and non-natural resource-rich provinces. Findings: This study found that expenditure inequality and polarization in Indonesia have moved in line, showing an increasing trend during the observation period. In the regional context, the greatest rise was in the region with low initial levels of expenditure inequality and polarization. The trends in each of the regional dimension showed a convergent pattern. It also showed that a significant portion of total polarization was attributed to expenditure differences between urban and rural areas rather than the other groups of regions. Research limitations/implications: The similar upward movement of expenditure inequality and polarization indicates that not only the differences between groups of expenditure are getting larger, but also the identification of the within groups expenditure are getting stronger. Since the high degree of inequality and polarization are closely related to conflict among groups of communities, this finding is a strong message to the policymaker that the development process in Indonesia during 2002–2012 tended to encourage the creation of social instability. Practical implications: This study provides an evaluation for further development of social economy in Indonesia. Originality/value: This paper attempts to give an overview of the relationship between expenditure inequality and polarization in Indonesia during 2002–2012. It also tries to reveal in which regional dimension, expenditure inequality and polarization occurred in Indonesia during the mentioned period. The issues have not been examined in previous empirical studies in Indonesia.